Comparative analysis between four models of IoT gateway selection - Ritu, Ananya; Tanha, Pohali Mahjabin; Islam, Wasema Nooren; Islam, Sumaiya Ferdous (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.